Leaf anatomical traits are correlated with tree dominance in a Neotropical deciduous forest - Rossatto, D. R.; Kolb, R. M. (Wiley, 2013)
Deciduous forests from the neotropics are one of the most endangered forest types in the world due to the exploitation of their natural resources by mankind. Many aspects of these ecosystems have been studied; however, there is a lack of information about leaf structure and the effects of tree dominance on their structural leaf patterns. In this article, we examine leaf anatomy and specific leaf areas (SLA) in 13 tree species differing in their dominance in a Dry Forest site in Central Brazil, relating leaf anatomical traits with phytosociological aspects. Leaf anatomical traits differed according to tree dominance: greater leaf thickness (achieved through greater thickness of the mesophyll), low values of SLA and bigger stomata were found for the most dominant species, whereas the less dominant species showed thinner leaves with high SLA, as well as numerous and small stomata. These responses suggest that tree dominance is an important indirect effect associated with vertical light availability in the forest. These strategies are probably related to the accomplishment of a high performance in carbon gain and water economy, given the distinction in irradiance that the leaves of different species are subject to in the dry forest. © 2013 Copyright The Royal Society of New Zealand.
Keywords: deciduous trees; dry forest; functional traits; leaf anatomy; tree dominance